Effects of Intermittent Air Velocity on Thermal and Draught Perception During Transient Temperature Conditions - WigÖ, Hans (The International journal of ventilation, 2008)
Previous research has shown that air movement has a significant influence on humans' thermal comfort. For persons feeling cool, air movement tends to be perceived as draught, whilst when feeling warm air movements may provide a desired cooling effect. In the transition zone it therefore seems difficult to use constant air velocity as a tool for cooling without creating draught problems. Nevertheless, from an energy saving perspective it appears to be far more efficient to use enhanced convective cooling, induced by the air movement, to cool only the occupants instead of the entire building. One possible way to use air movement as a method to improve thermal comfort without resultant draught problems could be to use intermittent air velocity instead of constant velocity. The present paper reports results from three experiments where subjects have been exposed to velocity variations, showing support for the hypothesis that it is possible to cool humans and reduce the percentage of occupants who are dissatisfied with the room temperature, without creating draught problems, through intermittent cooling.